IMPLEMENTASI MODEL PEMBELAJARAN STAD DALAM MENINGKATKAN HASIL BELAJAR PENDIDIKAN AGAMA KATOLIK SISWA SMP ST YOSEPH MEDAN - Tibo, Paulinus; Tarigan, Agnes Monika (CREDENDUM: Jurnal Pendidikan Agama, 2024)
This research aims to analyze the implementation of the STAD (Student Teams Achievement Division) learning model in improving student learning outcomes in Catholic Religious Education at St. Yoseph Middle School, Medan. The study was conducted at St. Yoseph Middle School using a qualitative approach. A total of 10 informants, consisting of teachers, students, and educational staff, were selected as primary data sources. Data were collected through direct observation, in-depth interviews with informants, and documentation of learning activities. The findings indicate that the application of the STAD model enhances student motivation, active participation in group discussions, and their understanding of Catholic religious teaching material. Interaction and collaboration within groups encourage students to express their opinions more confidently and assist each other in comprehending the material. However, challenges such as differing levels of understanding among group members can be addressed through teacher guidance. This research demonstrates that the STAD learning model is effective in creating an interactive learning environment and improving students' learning outcomes in Catholic Religious Education.